Analisis Angka Partisipasi PAUD Untuk Mewujudkan Pendidikan Berkualitas di Provinsi Riau - Eva Eriani; Anne Mudya Yolanda (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2022)
Quality education can be traced back to the level of early childhood education as assessed by the participation rate in Early Childhood Education (ECE). The ECE participation rate is determined by three indicators: the School Participation Rate (SPR), the Gross Enrollment Rate (GER), and the Pure Participation Rate (PPR). However, there are still gaps in the national ECE participation rate, children who have not earned ECE services, and some villages that do not have ECE institutions. Although the Ministry of Education and Culture has established guidelines for one village one ECE. The purpose of this research is to provide an overview of ECE participation rates in Riau Province and to explain what factors influence them. This study used descriptive analysis. Secondary data were obtained from the Central Bureau of Statistics, the Ministry of Education and Culture, and the Ministry of National Development Planning/National Development Planning Agency. The results show that the ECE participation rate, in general, has been fluctuating, especially in the last five years, and that the GER of children attending ECE in Riau province is still lower than the national rate, while the PPR in rural areas is higher than the NER in urban areas. According to PER by gender, girls who attend ECE on time contribute more than boys. Those are influenced by the fact that ECE institutions are not recorded in the education database, and there are social trends that lead parents to prefer homeschooling over ECE institutions, particularly with the impact of the COVID-19.